VEGETATIVE PROPAGATION OF SELECTED BALETE SPECIES IN ARGAO, CEBU - Alburo, Hemres M.; Alburo, Rosalyn P.; Pascual, Pet Roey L. (Journal of Agriculture and Technology Management, 2018)
Please see PDF file.